Gesundheit von LGBT-Personen in der Schweiz Unter Mitarbeit von Stefanie C. Boulila | David Garcia Nuñez | Laurent Michaud | Irene Müller | Rafael Traber - Krüger, Paula (Sexualität, Gesundheit und Gesellschaft. Sexuality, Health and Society, 2023)
This Swiss study identifies areas where LGBTQ+ people have unequal health opportunities compared to the general population, including mental and sexual health, discrimination and violence, barriers to healthcare and substance use. Using data from the Swiss Health Survey (2012, 2017) and a large-scale national survey of LGBTQ+ people conducted in 2021, the authors identify differences in health status as well as behaviour which promotes and is detrimental to health. The study also includes a review of the current research literature on this topic and concludes with recommendations on how to strengthen the health of LGBTQ+ people.